A Mechanistic Investigation of Acid-Catalyzed Cleavage of Aryl-Ether Linkages: Implications for Lignin Depolymerization in Acidic Environments - Sturgeon, MR; Kim, S; Lawrence, K; Paton, R; Chmely, S; Nimlos, M; Foust, T; Beckham, G (2014)
Acid catalysis has long been used to depolymerize plant cell wall polysaccharides, and the mechanisms by which acid affects carbohydrates have been extensively studied. Lignin depolymerization, however, is not as well understood, primarily due to the heterogeneity and reactivity of lignin. We present an experimental and theoretical study of acid-catalyzed cleavage of two non-phenolic and two phenolic dimers that exhibit the β-O-4 ether linkage, the most common intermonomer bond in lignin. This work demonstrates that the rate of acid-catalyzed β-O-4 cleavage in dimers exhibiting a phenolic hydroxyl group is 2 orders of magnitude faster than in non-phenolic dimers. The experiments suggest that the major product distribution is similar for all model compounds, but a stable phenyl-dihydrobenzofuran species is observed in the acidolysis of two of the γ-carbinol containing model compounds. The presence of a methoxy substituent, commonly found in native lignin, prevents the formation of this intermediate. Reaction pathways were examined with quantum mechanical calculations, which aid in explaining the substantial differences in reactivity. Moreover, we use a radical scavenger to show that the commonly proposed homolytic cleavage pathway of phenolic β-O-4 linkages is unlikely in acidolysis conditions. Overall, this study explains the disparity between rates of β-O-4 cleavage seen in model compound experiments and acid pretreatment of biomass, and implies that depolymerization of lignin during acid-catalyzed pretreatment or fractionation will proceed via a heterolytic, unzipping mechanism wherein β-O-4 linkages are cleaved from the phenolic ends of branched, polymer chains inward toward the core of the polymer. © 2013 American Chemical Society.